Assessment of Trigger Points therapy effectiveness with positional release method among office workers - Radosław Boćkowski; Magdalena Gębska (Kazimierz Wielki University, 2019)
Introduction: Cervical spine pain is one of the most common health problems among adults. The factors contributing to cervical pain include: improper musculoskeletal system strain (lack of ergonomics), absence of active rest and proper prevention. Because of incorrect exploitation TrP (trigger points) creation occurs in soft tissues. One of the cervical spine pain healing methods is TrPs therapy with positional release method. Aim: The aim of the study was assessment of the effectiveness of TrPs deactivation with positional release method within selected cervical spine and shoulder girdle muscles among office workers. Material and methods: The study was carried out among 38 office workers of both sexes (44.74% male and 52.63% female) aged 26 to 61 reporting painfulness of cervical spine and shoulder girdle. In the study following methods, scales and tools were used: NDI (Neck Disability Index) to assess the degree of neck disability caused by cervical spine disorders, NRS (Numerical Rating Scale) to assess pain intensity and Wagner algometer to assess pain tolerance. The assessment was performed on: levator scapulae muscle, sternocleidomastoid muscle, trapezius muscle, oblique superior muscle and rectus capitis posterior major muscle. Afterwards a TrPs therapy with positional release method was performed. After the therapy an assessment with NDI scale and an algometer was performed once again. The results were developed with use of Statistica 12 Programme. Pearson's correlation was used in the statistical analysis. Results: 36.84% of the subjects were assumed to possess no disability, 44.74% possessed mild disability and 18.42% possessed moderate disability the NDI scale. After the levator scapulae muscle, sternocleidomastoid muscle, trapezius muscle, oblique superior muscle and rectus capitis posterior major muscle therapy pain intensity significantly decreased (p